Crecimiento empresarial en el Comercial Anny Center del Recinto Tres Postes periodo 2021. - Palma Rodríguez, Darlanne Melina (2022)
The growth of a company refers to an increase in the size of variables such as the size of assets, production, sales, profits or employment. It is one of the fundamental elements that defines a corporate strategy. Every organization aims to grow, expand and cover more markets; Within the Anny Center establishment, an analysis of the current situation of the company was carried out, instruments were created to comply with the techniques used in the research work. Business growth is about the process of allowing a company to continuously improve and drive the organization to achieve previously planned objectives or success milestones. For the Anny Center microenterprise, it is determined that the strategies to be applied for the differentiation of the establishment are: segmentation and positioning and it is recommended to implement Michael Porter's Growth Strategy, with its bases that are: Leadership in costs, differentiation and focus.